Analysis of Figurative Language in Lyrics of Song “Glimpse of Us” By Joji - Sitepu, Kristina; Sidabutar, Ribka Oktaviani; Sirait, Febrianto; Rajagukguk, Fretty Riana; Siregar, Christina Anita Elizabeth (International Journal Corner of Educational Research, 2023)
This research examines the figurative language in Joji’s captivating English song, “Glimpse of Us”. The research drew its source from the international song website, www.azlyrics.com. The researchers meticulously analyzed the findings using a qualitative approach with a descriptive design. Remarkably, the song revealed a rich tapestry of figurative language encompassing seven distinct types. Allegory, the dominant form, emerged seven times, while metaphor emerged three times. Hyperbole and symbol each made two appearances, lending further depth and nuance to the composition. Additionally, the song employed apostrophe, repetition, and synecdoche once each, contributing to its overall lyrical magnificence. In terms of percentage, allegory comprised an impressive 41%, metaphor accounted for 18%, hyperbole, and symbol contributed 12%, and apostrophe, repetition, and synecdoche each held 6%.